2015
DOI: 10.1111/sji.12252
|View full text |Cite
|
Sign up to set email alerts
|

Immune‐ and Ribosome‐Related Genes were Associated with Systemic Vasculitis

Abstract: This study aimed to investigate the molecular mechanism of systemic vasculitis via bioinformatics analysis. Gene express profile of E-GEOD-16945 (13 Takayasu arteritis samples and 13 control samples) was downloaded from European Bioinformatics Institute (EBI) database. Differentially expressed genes (DEGs) were screened between Takayasu arteritis and normal controls (|log FC| > 1). Basic local alignment search tool (BLASTX) was used for the Clusters of Orthologous Groups (COG) classification of DEGs. Gene onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…A similar study showed that the ribosome pathway might be associated with inflammation [ 54 ]. Moreover, results of Li et al's study indicated that selected DEGs in psoriasis were enriched in the ribosomal pathway [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar study showed that the ribosome pathway might be associated with inflammation [ 54 ]. Moreover, results of Li et al's study indicated that selected DEGs in psoriasis were enriched in the ribosomal pathway [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the ribosomal proteins synthesis is closely related to the growth and proliferation of tumor cells during tumorigenesis [9,10] . Recently, studies have found that ribosomes and immune-related genes are associated with systemic vasculitis [11] . However, studies on ribosomal proteins, immune-related genes and VTE are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the ribosomal proteins synthesis is closely related to the growth and proliferation of tumor cells during tumorigenesis [13,14] . Recently, studies have found that ribosomes and immune-related genes are associated with systemic vasculitis [15] . However, studies on ribosomal proteins, immune-related genes and VTE are rarely reported.…”
Section: Introductionmentioning
confidence: 99%